2017
DOI: 10.5751/ace-00957-120105
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing density of the Northern Mealy Amazon in three forest types of a modified rainforest landscape in Mesoamerica

Abstract: ABSTRACT. The high rate of conversion of tropical moist forest to secondary forest makes it imperative to evaluate forest metric relationships of species dependent on primary, old-growth forest. The threatened Northern Mealy Amazon (Amazona guatemalae) is the largest mainland parrot, and occurs in tropical moist forests of Mesoamerica that are increasingly being converted to secondary forest. However, the consequences of forest conversion for this recently taxonomically separated parrot species are poorly unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…Our results are consistent with other studies that demonstrated that forest cover—a proxy of habitat amount and the most used landscape composition variable—has stronger effects on the abundance or occurrence of bird species in tropical forests (Bonfim et al, 2021; Carrara et al, 2015; Cerezo et al, 2010; Morante-Filho et al, 2021). Results from this study also support other studies which have demonstrated that some parrot species are more abundant within preserved sites with highest forest cover (De Labra-Hernandez & Renton, 2017; Legault et al, 2011). An increasing number of individuals of both toucans and parrots with higher amount of forest is likely explained by the high resource availability for large-bodied cavity nesting birds, like toucans and parrots, in forest habitats (Cornelius et al, 2008; De Labra-Hernández & Renton, 2016; Zanette et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with other studies that demonstrated that forest cover—a proxy of habitat amount and the most used landscape composition variable—has stronger effects on the abundance or occurrence of bird species in tropical forests (Bonfim et al, 2021; Carrara et al, 2015; Cerezo et al, 2010; Morante-Filho et al, 2021). Results from this study also support other studies which have demonstrated that some parrot species are more abundant within preserved sites with highest forest cover (De Labra-Hernandez & Renton, 2017; Legault et al, 2011). An increasing number of individuals of both toucans and parrots with higher amount of forest is likely explained by the high resource availability for large-bodied cavity nesting birds, like toucans and parrots, in forest habitats (Cornelius et al, 2008; De Labra-Hernández & Renton, 2016; Zanette et al, 2000).…”
Section: Discussionsupporting
confidence: 91%